Pengaruh Konseling Kelompok REBT Dengan Teknik Journaling Untuk Mengurangi Kecanduan Pornografi - Purwanti, Purwanti; Supriyatna, Arie; Indiati, Indiati (Borobudur Counseling Review, 2021)
This study aims to determine the effect of REBT group counseling with journaling techniques in reducing pornography addiction in class XI students of SMA Negeri 1 Candiroto Temanggung. This study used a one group pretest posttest design. The research subjects were selected by perposiv sampling. The research sample consisted of 10 students who were included in the experimental group. Collecting data using observations and a questionnaire on pornography addiction. The data analysis technique used the Wilcoxon test with the help of SPSS for windows version 16.0. The results showed that the journaling technique group counseling had an effect on pornography addiction to the XI grade students of SMA Negeri 1 Candiroto Temanggung. This is evidenced by the difference in the average score of the experimental group pornography addiction scale. The results of the decrease in the pretest and posttest scores were the highest score of 54 or (29.8%) and the lowest was 22 or (14.2%). The average pretest and posttest pornography addiction was 33.8 or (21.4%). The more the students' pornography addiction scale score decreased, it proved that the effect of group counseling with journaling techniques could reduce pornography addiction in the experimental class.